Intégration du développement durable par les principes et la démarche de conception dans un cours projet - Anouk Desjardins; Louise Millette; Eric Bélanger (VertigO)
The course ING4901 - Sustainable Development Capstone Project is a pluridisciplinary, last-year undergraduate project course offered to engineering students from all programs at École Polytechnique de Montréal. Since the term fall 2009, students in architecture who had registered for final-year undergraduate course ARC3012B – Workshop form and technique were integrated into the teams of engineering students. A teacher from the School of Architecture joined the teaching team to supervise the architecture students. The course ING4901 aims to integrate sustainable development into the educational background and demonstrate that all engineers and architects should be concerned with sustainable development no matter what their field of practice. In addition to incorporating technical concepts learned during the bachelor’s program the course introduces students to integrated process design, a practice that is increasingly common in the design of green buildings. A foundation of sustainable development, integrated process design may be difficult to apply but can ensure a project’s success, as the constraints and goals of all disciplines involved are considered from the beginning of the project. Through course activities and support, teachers encourage students to work together and avoid working in silo despite the different technical languages of team members. Teachers supervise the students’ design process, organize activities involving professionals from different fields to provide students with technical support, and guide students in addressing all aspects of sustainable development.